Non-intumescent fire retardant coating for fiber reinforced composite material as well as preparation method and application of non-intumescent fire retardant coating
By using non-expanded fire-retardant coatings on fiber-reinforced composite materials, combining adhesives, thermally insulated fillers and flame retardants, the coating with high temperature strength and thermal insulation performance is solved, and the protection effect of existing fire-retardant coatings at high temperatures is not achieved. The best problem significantly improves the fire resistance and thermal insulation properties of the FRP reinforced structure.
Patent Information
- Application Number
- CN202411495614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing fire-retardant coatings used for fiber-reinforced composite materials have limited protection effect in high temperature environments and cannot meet the fire resistance requirements of FRP reinforced structures, resulting in fire safety hazards.
Non-expanded fire-retardant coatings, containing binders, heat-insulating fillers, flame retardants and fibers, are used to form coatings with high temperature strength and thermal insulation properties through specific ratios and preparation methods, including metakaolin, fly ash, CA80 high-aluminum cement, aluminum hydroxide, magnesium hydroxide, glass fiber and other components form multi-size porous structures to improve the thermal insulation and mechanical properties of the coating.
It significantly improves the fire resistance and thermal insulation performance of the FRP reinforced structure at high temperatures, extends the temperature platform period, reduces the harm and losses caused by fire, and ensures that the structure continues to play a mechanical role in the fire.
Smart Images

Figure BDA0005101180000000131 
Figure BDA0005101180000000161 
Figure BDA0005101180000000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fireproof materials, and in particular relates to a non-expansive fireproof coating for fiber-reinforced composite materials, and a preparation method and application thereof. Background Art
[0002] In recent years, fiber reinforced plastics (FRP) have become a popular material in reinforcement projects due to their light weight, high strength, good durability and convenient construction. Although the FRP reinforcement method has many advantages, its major drawback is its poor high temperature resistance. Currently, most of the adhesives used to bond FRP materials are epoxy resin polymers. However, studies have shown that the mechanical properties of such adhesives will drop significantly after exceeding 120°C, resulting in insufficient fire resistance of FRP reinforced concrete components that have not been fireproofed in a fire, and cannot meet the requirements of relevant fire resistance specifications, thus posing a hidden danger to the fire safety of the structure.
[0003] In order to improve the fire resistance of FRP reinforced structures, fireproof panels or fireproof coatings are usually used for protection, among which non-expanding fireproof coatings are the most widely used. Although these coatings can effectively extend the fire resistance limit of reinforced concrete structures to meet the requirements of the specifications, the protective effect on FRP adhesives is still not ideal. In a high temperature environment, the temperature at the FRP quickly exceeds 120°C, causing the mechanical properties of the epoxy resin to drop significantly and lose its due force transmission function. This shows that although the fire-retardant coating delays the degradation of the performance of reinforced concrete, its protective effect on the FRP reinforcement system is limited, and the special needs of FRP materials are not fully considered.
[0004] At present, FRP materials have been widely used in the field of building reinforcement, but the research on corresponding fire-retardant coatings has lagged behind significantly. It is urgent to conduct more in-depth research on the fire protection of FRP materials in order to improve the overall fire resistance of FRP reinforced structures. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a non-expanding fire retardant coating for fiber reinforced composite materials, and a preparation method and application thereof. The coating formed by the non-expanding fire retardant coating provided by the present invention has excellent thermal insulation performance and high-temperature strength, and can be used as a fire retardant coating for fiber reinforced composite materials (FRP).
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a non-expanding fire-retardant coating for fiber-reinforced composite materials. The raw materials for preparation include, by weight percentage, 50-58% of a binder, 20-24% of a heat-insulating filler, 5-10% of a flame retardant, 0.3-0.5% of a fiber, 0.3-0.6% of an auxiliary agent, and 12-15% of water.
[0008] The binder includes metakaolin, fly ash, CA80 high-alumina cement and an activator, or includes metakaolin, fly ash, CA80 high-alumina cement, an activator and an organic binder;
[0009] The organic binder includes redispersible latex powder and / or polyvinyl alcohol powder;
[0010] The heat-insulating filler includes expanded vermiculite, hydrophobically modified expanded perlite, sepiolite and hollow glass microspheres;
[0011] The flame retardant includes aluminum hydroxide and magnesium hydroxide;
[0012] The fibers include glass fibers;
[0013] The auxiliary agents include a foaming agent, a thickener, a foam stabilizer and acrylic emulsion.
[0014] Preferably, the particle size of the hydrophobically modified expanded perlite is 1 to 2 mm; the hydrophobically modified expanded perlite is isobutyltriethoxysilane modified expanded perlite.
[0015] Preferably, the hollow glass microspheres include two types of hollow glass microspheres with a particle size of D50 = 65 μm and a particle size of D50 = 40 μm; the volume ratio of the two types of hollow glass microspheres with a particle size of D50 = 65 μm and a particle size of D50 = 40 μm is 5-7:3-5.
[0016] Preferably, the foaming agent includes sodium α-olefin sulfonate; the foam stabilizer includes calcium stearate and / or a lightweight partition board foam stabilizer; and the thickener includes cellulose ether.
[0017] Preferably, the mass ratio of the foaming agent to the thickener is 0.1-0.3:0.07; the mass ratio of the foaming agent to the foam stabilizer is 0.1-0.3:0.5; the mass ratio of the foaming agent to the acrylic emulsion is 0.1-0.3:1, and the solid content of the acrylic emulsion is 40-60%.
[0018] Preferably, the mass ratio of the metakaolin to the redispersible latex powder is 70:0-5; the mass ratio of the metakaolin to the polyvinyl alcohol powder is 70:0-1.5.
[0019] Preferably, the mass ratio of the metakaolin, fly ash and CA80 cement is 50-70:20-48:2-3; the mass ratio of the metakaolin and the activator is 70:123-135.
[0020] The present invention also provides a method for preparing the non-expanding fire retardant coating for fiber-reinforced composite materials according to the above technical solution, comprising the following steps:
[0021] A binder other than the activator, a heat-insulating filler other than the hollow glass microspheres, and a flame retardant are first mixed to obtain a base material;
[0022] The base material, foaming agent, thickener and foam stabilizer are mixed for the second time to obtain a dry material;
[0023] The dry material and hollow glass microspheres are mixed for a third time, and then an activator, acrylic emulsion and water are added for a fourth mixing to obtain a mixture;
[0024] The mixed material and the fibers are mixed and dispersed to obtain a non-expanding fire retardant coating for fiber-reinforced composite materials.
[0025] The present invention also provides the use of the non-expanding fire retardant coating for fiber-reinforced composite materials described in the above technical solution or the non-expanding fire retardant coating for fiber-reinforced composite materials prepared by the preparation method described in the above technical solution in fire prevention of fiber-reinforced composite materials.
[0026] The present invention also provides a method for preparing a non-expanding fire retardant coating, comprising the following steps: coating a non-expanding fire retardant coating for fiber-reinforced composite materials on the surface of a concrete structure reinforced with fiber-reinforced composite materials, and performing curing to obtain a non-expanding fire retardant coating;
[0027] The non-expanding fire retardant coating for fiber-reinforced composite materials is the non-expanding fire retardant coating for fiber-reinforced composite materials described in the above technical solution or the non-expanding fire retardant coating for fiber-reinforced composite materials prepared by the preparation method described in the above technical solution.
[0028] The invention provides a non-expanding fireproof coating for fiber-reinforced composite materials. The raw materials for preparation include, by weight percentage, 50-58% of a binder, 20-24% of a heat-insulating filler, 5-10% of a flame retardant, 0.3-0.5% of fiber, 0.3-0.6% of an auxiliary agent and 12-15% of water; the binder includes metakaolin, fly ash, CA80 high-alumina cement and an activator, or includes metakaolin, fly ash, CA80 high-alumina cement, an activator and an organic binder; the organic binder includes redispersible latex powder and / or polyvinyl alcohol powder; the heat-insulating filler includes expanded vermiculite, hydrophobically modified expanded perlite, sepiolite and hollow glass microspheres; the flame retardant includes aluminum hydroxide and magnesium hydroxide; the fiber includes glass fiber; the auxiliary agent includes a foaming agent, a thickener, a foam stabilizer and acrylic emulsion.
[0029] The coating formed by the non-expanding fire-retardant coating for fiber-reinforced composite materials provided by the present invention contains pores of three sizes, which is beneficial to the improvement of thermal insulation performance. First, the geopolymer gelling material generated by the reaction of metakaolin, fly ash, CA80 cement and an activator has a large number of nano-scale gel pores; secondly, the addition of hollow glass microspheres can introduce micron-scale pores in the coating to further improve the thermal insulation performance of the coating, and can also improve the fluidity of the coating. A foaming agent is added to the coating to form micron or even millimeter-scale pores in the coating. The foaming agent can not only introduce pores to improve the thermal insulation performance, but also reduce the amount of water used in the preparation. The flame retardant decomposes under heat, absorbs heat, reduces the temperature rise trend of building components, and is also beneficial to improving the thermal insulation performance of the coating. In addition, the addition of hydrophobically modified expanded perlite greatly reduces the water consumption and improves the strength of the geopolymer binder matrix skeleton. Therefore, under the action of high temperature, the ability of the pore wall in the coating to resist the expansion stress caused by water evaporation and the stress caused by sintering shrinkage is improved, thereby enhancing the ability of the coating structure to resist thermal stress, thereby improving the strength of the coating at high temperature (800℃), enabling it to better protect the FRP reinforced concrete system. In addition, when exposed to fire, a significant temperature (100℃) plateau period will appear, and the time below 120℃ is nearly one hour. This is very beneficial for the FRP reinforced concrete system to continue to play a mechanical role under fire, so that it will not be destroyed in a short time after the fire, effectively reducing the harm and loss of the structure caused by fire. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the compression test diagram;
[0031] Figure 2 This is the bending test diagram;
[0032] Figure 3 This is the bonding strength direct pull test diagram;
[0033] Figure 4 This is a water resistance test diagram;
[0034] Figure 5 This is a schematic diagram of the fire resistance test;
[0035] Figure 6 This is a comparison chart of the fire resistance of the non-expanding fire retardant coatings for fiber-reinforced composite materials prepared in Examples 1 to 3 and the fire retardant coating of Comparative Example 4. DETAILED DESCRIPTION
[0036] The present invention provides a non-expansion fireproof coating for fiber-reinforced composite materials, which is prepared by raw materials, in terms of mass percentage, including 50-58% of binder, 20-24% of heat-insulating filler, 5-10% of flame retardant, 0.3-0.5% of fiber, 0.3-0.6% of auxiliary agent and 12-15% of water;
[0037] The binder includes metakaolin, fly ash, CA80 high-alumina cement and an activator, or includes metakaolin, fly ash, CA80 high-alumina cement, an activator and an organic binder;
[0038] The organic binder includes redispersible latex powder and / or polyvinyl alcohol powder;
[0039] The heat-insulating filler includes expanded vermiculite, hydrophobically modified expanded perlite, sepiolite and hollow glass microspheres;
[0040] The flame retardant includes aluminum hydroxide and magnesium hydroxide;
[0041] The fibers include glass fibers;
[0042] The auxiliary agents include a foaming agent, a thickener, a foam stabilizer and acrylic emulsion.
[0043] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used in the preparation, and commercially available products known to those skilled in the art can be used.
[0044] The raw materials for preparing the non-expanding fire retardant coating for fiber-reinforced composite materials provided by the present invention include a binder with a mass percentage of 50-58%, preferably 54%. In the present invention, the binder includes metakaolin, fly ash, CA80 high-alumina cement and an activator, or includes metakaolin, fly ash, CA80 high-alumina cement, an activator and an organic binder.
[0045] In the present invention, the particle size of the metakaolin is preferably 0.4-50 μm, and more preferably D50 particle size = 14 μm; the particle size of the fly ash is preferably 0.32-57 μm, and more preferably D50 particle size = 7.8 μm; the particle size of the CA80 high-alumina cement is preferably 1-50 μm, and more preferably D50 particle size = 14.5 μm; the activator is preferably an alkali activator; the alkali activator is preferably a mixed solution of sodium silicate and sodium hydroxide; the mass ratio of sodium silicate to sodium hydroxide is 2:1; the modulus of the activator is preferably 1.5-2M, and more preferably 1.6M.
[0046] In the present invention, the mass ratio of the metakaolin, fly ash and CA80 cement is preferably 50-70:20-48:2-3, more preferably 70:27.5:2.5; the mass ratio of the metakaolin and the activator is preferably 70:123-135, more preferably 70:135.
[0047] In the present invention, the organic binder preferably includes redispersible latex powder and / or polyvinyl alcohol powder, more preferably redispersible latex powder and polyvinyl alcohol powder; the particle size of the redispersible latex powder is preferably 1-7 μm, more preferably 3-5 μm; the particle size of the polyvinyl alcohol powder is preferably 120 mesh; the number average molecular weight of the polyvinyl alcohol powder is preferably 72600-81400, more preferably 80000; the mass ratio of the metakaolin and the redispersible latex powder is preferably 70:0-5, more preferably 70:2-5; the mass ratio of the metakaolin and the polyvinyl alcohol powder is preferably 70:0-1.5, more preferably 70:0.5-1.5.
[0048] In the present invention, the geopolymer cementitious material generated by the reaction of metakaolin, fly ash, CA80 high-aluminum cement and activator has a large number of nano-scale gel pores and adsorbs a certain amount of free water. It absorbs heat by evaporation at high temperature, which is beneficial to heat insulation. The higher the amount of metakaolin, the better the density and fire resistance of the coating will be, because the geopolymer structure helps to prevent the conduction of heat. However, too much metakaolin may affect the flexibility and adhesion of the coating. Increasing the amount of fly ash can improve the fluidity and workability of the coating and reduce the risk of shrinkage cracks. However, fly ash has low reactivity, and too much fly ash may cause the mechanical properties and fire resistance of the coating to decrease, especially under high temperature conditions, it may affect its stability. Increasing the amount of CA80 high-aluminum cement can usually improve the high temperature resistance and mechanical strength of the coating. However, too much cement may increase the brittleness of the coating, affecting its bonding performance and thermal expansion characteristics. Usually, its dosage is controlled within a certain range (such as 1-5%) to achieve the best balance. The amount of activator directly affects the formation speed and strength of the geopolymer. If the amount of activator is too low, the geopolymerization reaction is not sufficient, and the hardening and strength of the coating will be poor; if the amount of activator is too high, although it can improve the reaction efficiency, it may increase the brittleness of the coating and affect the fire resistance. Therefore, the amount of activator needs to be precisely adjusted according to the amount of kaolin and fly ash to obtain the appropriate hardening speed and strength.
[0049] Redispersible polymer powder and polyvinyl alcohol can improve the bonding strength of the coating. Redispersible polymer powder (RDP) is a polymer-modified material with excellent bonding and flexibility. In fire-retardant coatings, it can enhance the toughness, crack resistance and adhesion of the coating, while improving the workability of the coating. In addition, RDP can form a waterproof film, which helps to improve the water resistance of the coating and prevent the coating from absorbing water and swelling or failing in a humid environment. Although RDP can improve the overall performance of the coating, it is essentially an organic polymer with limited high temperature resistance. At high temperatures, RDP will decompose or soften, which may affect the high temperature stability of the fire-retardant coating. Therefore, the amount of RDP needs to be controlled within a reasonable range to take into account both bonding and fire resistance.
[0050] Polyvinyl alcohol (PVA) is a water-soluble polymer that is often used to enhance the adhesion and crack resistance of coatings. It can form a stable network structure with other inorganic materials to enhance the mechanical strength of the coating. The introduction of PVA can improve the adhesion strength of the coating, especially in low temperature or high humidity environments, and can effectively prevent the coating from falling off. PVA increases the adhesion between the coating and the substrate by forming a thin film. PVA has good flexibility in the coating system, can absorb stress in the coating, reduce crack formation during the drying process, and improve the toughness and stability of the coating. PVA is an organic material. Although it can significantly improve the mechanical properties and workability of the coating in the initial stage, its high temperature resistance is limited. At temperatures exceeding 200°C, PVA will undergo thermal decomposition or carbonization, which may cause the coating to fail under extreme high temperature conditions. Therefore, the amount of PVA is usually limited to 1-3% to avoid affecting the fire resistance.
[0051] The raw materials for preparing the non-expanding fire-retardant coating for fiber-reinforced composite materials provided by the present invention include 20-24% by weight of thermal insulation filler, preferably 21-23%, and more preferably 22.2%. In the present invention, the thermal insulation filler includes expanded vermiculite, hydrophobically modified expanded perlite, sepiolite and hollow glass microspheres.
[0052] Expanded vermiculite is a natural mineral material that expands in volume after high-temperature treatment. It has excellent thermal insulation, fire resistance and light density. In fire-retardant coatings, its main function is to improve the fire resistance and thermal insulation of the coating. Expanded vermiculite can effectively expand at high temperatures to form a porous structure, which slows down the transfer of heat to the substrate. Therefore, increasing the amount of expanded vermiculite can significantly improve the fire resistance of the coating. However, since expanded vermiculite itself is relatively fragile, excessive dosage may lead to a decrease in the mechanical strength of the coating, especially the compressive strength and impact resistance. Therefore, the amount of expanded vermiculite usually needs to be controlled to balance fire resistance and mechanical strength.
[0053] Hydrophobically modified expanded perlite is a lightweight porous material that has been hydrophobically treated and has good thermal insulation, fire resistance and hydrophobic properties. The hydrophobic treatment enhances its stability in a humid environment, making it less likely to absorb water and maintaining good structural properties. The introduction of hydrophobically modified expanded perlite can improve the water resistance of fire retardant coatings, prevent the coating from absorbing water and swelling in a humid environment, and maintain the integrity of the coating. The porous structure of expanded perlite is similar to that of expanded vermiculite, which can effectively block heat conduction and improve the thermal insulation effect of the coating. Properly increasing the amount of perlite added can help improve the fire resistance of the coating. Expanded perlite itself is brittle, and too high an amount may cause the strength of the coating to decrease, especially the compression and wear resistance.
[0054] Sepiolite is a fibrous mineral rich in hydrated magnesium silicate, which has high heat resistance and good thermal insulation properties. Its fibrous structure helps to enhance the adhesion and crack resistance of the coating. The high fire resistance and low thermal conductivity of sepiolite enable it to effectively reduce heat transfer in high temperature environments while maintaining structural stability under fire conditions. The fibrous structure of sepiolite can form a network reinforcement system in the coating, improve the crack resistance and impact resistance of the coating, and reduce the risk of cracking and peeling at high temperatures. Sepiolite also has a certain adsorption capacity, which can improve the cohesion of the coating and enhance the stability of the coating. The dosage is generally between 5% and 10% to have a positive effect on the performance of the coating. Excessive dosage may cause the coating to deteriorate in workability or generate internal stress.
[0055] Hollow glass microspheres are tiny hollow spherical particles with light weight, low thermal conductivity and high temperature resistance. They are often used to improve the thermal insulation performance of coatings and reduce coating density. The low density of hollow glass microspheres can significantly reduce the overall weight of the coating, making them suitable for thick coatings or large-area fire-retardant coatings to reduce the additional load caused by weight. Due to their hollow structure, hollow glass microspheres can effectively reduce heat conduction, improve the thermal insulation performance of coatings, and prevent heat from being quickly transferred to the substrate. Increasing the amount of hollow glass microspheres can improve the thermal insulation and fire resistance of coatings, but if used in excessive amounts, it may affect the mechanical strength of the coating, especially its compression and impact resistance.
[0056] In the present invention, the particle size of the expanded vermiculite is preferably 68 to 564 μm, and more preferably D50 particle size = 226.6 μm; the particle size of the hydrophobically modified expanded perlite is preferably 1 to 2 mm; the hydrophobically modified expanded perlite is isobutyl triethoxysilane-modified expanded perlite; the preparation method of the isobutyl triethoxysilane-modified expanded perlite is preferably to hydrophobically modify the expanded perlite using isobutyl triethoxysilane; the concentration of the isobutyl triethoxysilane is 5wt%; the particle size of the sepiolite is preferably 300 to 400 μm, more preferably 350-400 μm; the hollow glass microspheres preferably include two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm; the volume ratio of the two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm is preferably 5-7:3-5, more preferably 7:3; the wall thickness of the hollow glass microspheres is preferably 1-3 μm, more preferably 2 μm; the true density of the hollow glass microspheres with a D50 particle size of 40 μm is preferably 0.59-0.63 g / cm 3 , more preferably 0.6 g / cm 3 The bulk density is preferably 0.33 to 0.36 g / cm 3 , more preferably 0.35 g / cm 3The actual density of hollow glass microspheres with a particle size of D50 = 65 μm is preferably 0.19 to 0.23 g / cm 3 , more preferably 0.2 g / cm 3 The bulk density is preferably 0.09 to 0.12 g / cm 3 , more preferably 0.1 g / cm 3 .
[0057] In the present invention, the mass ratio of the expanded vermiculite to the hollow glass microspheres is preferably 43.8:17.4-21.6, more preferably 43.8:17.4; the mass ratio of the hydrophobically modified expanded perlite to the hollow glass microspheres is preferably 22.5:17.4-21.6, more preferably 22.5:17.4; the mass ratio of the sepiolite to the hollow glass microspheres is preferably 15.4:17.4-21.6, more preferably 15.4:17.4.
[0058] In the present invention, first, the density of expanded vermiculite and hydrophobically modified expanded perlite is low, which can effectively reduce the density of fire retardant coating. In addition, the interior of expanded vermiculite is a cavity structure, and its pore size is micron-level and has a layered structure, which has good thermal insulation performance. Hydrophobically modified expanded perlite also has a porous microstructure and has an extremely low water absorption rate. The advantages of adding hydrophobically modified expanded perlite are mainly as follows: First, the pore structure of the modified expanded perlite is relatively closed, which reduces the pore damage caused by thermal stress when isolating heat, and improves the thermal insulation performance of fire retardant coating; Second, it can significantly reduce the amount of water, and reducing the amount of water can not only promote the hydration of geopolymer raw materials into a denser gel phase, but also improve the strength of the matrix. And the dense gel phase has more small capillaries, which can absorb more water and delay the heat conduction ability in the coating; Third, the lower water consumption can reduce the excessive foaming of the foaming agent, resulting in too large a proportion of connected pores in the coating, which cannot effectively isolate heat transfer, and will cause the coating strength to be too low, affecting daily use. Adding a low amount of CA80 cement is beneficial to promoting geopolymerization, and its hydration products can significantly improve the mechanical properties of the coating at high temperatures; sepiolite contains a large amount of fiber-like hydrated magnesium silicate with a large aspect ratio, which absorbs heat by evaporating water at high temperatures, which is beneficial to delaying the conduction of heat; in addition, sepiolite also has a certain toughening effect.
[0059] In the present invention, the hollow glass microspheres have a low thermal conductivity. The addition of the hollow glass microspheres can introduce micrometer-sized pores into the coating, thereby improving the thermal insulation performance of the coating, and can also improve the working performance of the coating.
[0060] The raw materials for preparing the non-expanding fire-retardant coating for fiber-reinforced composite materials provided by the present invention include a flame retardant with a mass percentage of 5 to 10%, more preferably 8 to 10%, and most preferably 9.4%. In the present invention, the flame retardant includes aluminum hydroxide and magnesium hydroxide; the mass ratio of the aluminum hydroxide to the magnesium hydroxide is preferably 1.5 to 2.5:1, more preferably 2:1.
[0061] In the present invention, the flame retardant decomposes under heat, which can absorb heat, reduce the temperature rise trend of building components, and is also beneficial to improve the thermal insulation performance of the coating. The decomposition temperature of magnesium hydroxide (350°C) is relatively high, so it is suitable for use in higher temperature fire protection environments, especially when the coating needs to maintain stability for a long time at high temperatures. The decomposition temperature of aluminum hydroxide (200°C) is relatively low, which is suitable for application scenarios that require rapid flame retardancy at the early stage of a fire. Whether it is magnesium hydroxide or aluminum hydroxide, although excessive dosage can improve the flame retardant effect, it may also lead to a decrease in the mechanical properties of the coating, such as increased brittleness or weakened adhesion. Therefore, the dosage needs to take into account the construction and mechanical strength of the coating while ensuring that the coating has good flame retardant properties. The synergistic use of magnesium hydroxide and aluminum hydroxide enables the aluminum hydroxide in the coating to provide an earlier flame retardant effect, while the magnesium hydroxide continues to work at higher temperatures, thereby extending the flame retardant time and improving the overall fire resistance.
[0062] The raw material for preparing the non-expanding fire-retardant coating for fiber-reinforced composite materials provided by the present invention comprises 0.3-0.5% by weight of fiber, preferably 0.4%. In the present invention, the fiber preferably comprises glass fiber; the length of the fiber is preferably 3-8 mm, more preferably 6 mm; the diameter of the fiber is preferably 5-20 μm, more preferably 10 μm.
[0063] Fiber length directly affects the reinforcement effect and crack resistance of the coating. Longer fibers can form a better reinforcement network in the coating, improving the overall strength and toughness of the coating. Longer fibers (such as 6-12 mm in length) can form a more stable three-dimensional reinforcement network, significantly improving the crack resistance and tensile strength of the coating. They can effectively disperse stress and reduce the risk of cracking of the coating at high temperatures or during drying. Although longer fibers contribute to the reinforcement effect, their excessive length may cause the fluidity and uniformity of the coating to deteriorate during construction, increasing the difficulty of construction. In order to ensure good construction performance, a moderate fiber length (such as 3-8 mm) is usually selected to strike a balance between reinforcement performance and construction convenience.
[0064] Secondly, the diameter of the fiber affects the dispersion of the fiber in the coating, the reinforcement effect and the overall density of the coating. Finer fibers are easy to disperse and can increase the density and uniformity of the coating. Finer fibers (such as those with a diameter of 10 to 20 μm) can be more evenly dispersed in the coating matrix, which helps to improve the density and crack resistance of the coating. At the same time, the addition of fine fibers can reduce local damage caused by stress concentration and improve the overall toughness of the coating. Although thicker fibers (such as those with a diameter of more than 50 μm) have a stronger reinforcement effect, they have poor dispersion and are prone to aggregation, affecting the uniformity of the coating. Thicker fibers may affect the workability of the coating, increase the thickness of the coating and reduce its smoothness. Therefore, in coatings that require high workability and smooth surfaces, fibers with smaller diameters are often used.
[0065] Reasonable fiber content can improve the crack resistance and tensile strength of the coating, but excessive use may lead to excessive density of the coating or difficulty in construction. With the increase of fiber content, the crack resistance, tensile strength and impact resistance of the coating are significantly improved. Fibers can effectively prevent the coating from cracking at high temperature or during drying by dispersing stress and forming a reinforcement network. In addition, fibers can enhance the impact resistance of the coating and improve the stability and durability of the coating at high temperatures. However, with the increase of fiber content, the fluidity and workability of the coating will decrease, and the coating may become more viscous and difficult to apply evenly.
[0066] The raw materials for preparing the non-expanding fire-retardant coating for fiber-reinforced composite materials provided by the present invention include 0.3-0.6% by weight of auxiliary agents, preferably 0.4-0.5%, more preferably 0.45%. In the present invention, the auxiliary agents include foaming agents, thickeners, foam stabilizers and acrylic emulsions.
[0067] In the present invention, the foaming agent preferably includes sodium α-olefin sulfonate.
[0068] The main function of the foaming agent is to reduce the density of the coating and enhance the thermal insulation of the coating by forming a foam structure. In fire retardant coatings, foaming agents can help form a lightweight, porous coating structure, thereby improving the thermal insulation performance of the coating. The main types of foaming agents are chemical foaming agents: such as carbonates and bicarbonates, which produce gas by high-temperature decomposition; and physical foaming agents: such as surfactants, which promote the formation of foam by reducing surface tension. The foaming agent forms a porous structure inside the coating by forming bubbles, reducing the thermal conductivity of the coating and enhancing the thermal insulation effect of the coating. When using chemical foaming agents, it is necessary to control their reaction rate and bubble size to avoid the generation of excessively large or unstable bubbles that affect the uniformity of the coating. However, excessive amounts of foaming agents may cause excessive foam, uneven holes inside the coating, and reduce the mechanical strength of the coating. Therefore, the amount of foaming agent should be moderate.
[0069] In the present invention, the thickener preferably includes cellulose ether.
[0070] Thickeners are used to adjust the viscosity of the coating and enhance the coating's construction performance and fluidity. It helps prevent the coating from sagging or dripping during construction and ensures the uniformity of the coating. The main types of thickeners are cellulose (HPMC, HEC) and acrylic polymer thickeners, which are widely used in water-based coatings. The use of thickeners can improve the fluidity of the coating, increase the operability during construction, reduce the problem of uneven coating caused by sagging during construction, and ensure uniform coverage of the coating. The addition of an appropriate amount of thickener can improve the coating's anti-sagging and surface smoothness. However, excessive use may cause the coating to be too viscous, affecting construction performance and the flexibility of the coating.
[0071] In the present invention, the foam stabilizer preferably includes calcium stearate and / or a lightweight partition board foam stabilizer, more preferably calcium stearate and a lightweight partition board foam stabilizer; the mass ratio of calcium stearate and lightweight partition board foam stabilizer is preferably 1:2 to 0.5, more preferably 1:1.
[0072] The main function of the foam stabilizer is to stabilize the foam structure generated by the foaming agent, prevent the bubbles from bursting too quickly, maintain the porous structure inside the coating, and ensure thermal insulation and fire resistance. There are mainly the following types of organic foam stabilizers: surfactants and polyvinyl alcohol substances, which help to form a stable foam film. The addition of foam stabilizers can significantly extend the life of the foam, ensure the uniformity of the foam structure inside the coating, and thus improve the thermal insulation and fire resistance of the coating. If there is not enough foam stabilizer, the foam is easy to burst, affecting the thermal insulation effect of the coating; but too much foam stabilizer may make the coating system too viscous, affecting the construction performance. Foam stabilizers help maintain the uniform distribution of bubbles in the coating, ensure the formation of a stable insulation layer in a high temperature environment, and thus improve the fire resistance of the coating.
[0073] In the present invention, the solid content of the acrylic emulsion is preferably 40-60%, more preferably 50%. In the present invention, the manufacturer of the lightweight partition board foam stabilizer is Luoyang Tongrun Nano Technology Co., Ltd.
[0074] As a matrix material, acrylic emulsion can give the coating good adhesion, flexibility and weather resistance. It can also improve the water resistance, alkali resistance and UV resistance of the coating, and is one of the important binders for fire retardant coatings. Acrylic emulsion can significantly improve the adhesion of the coating and ensure good adhesion between the coating and the substrate. It can also give the coating good flexibility and reduce cracking caused by temperature changes. Different types of emulsions have different water resistance and weather resistance. Pure acrylic emulsion performs better in outdoor protection and is suitable for fire retardant coating systems that are exposed to the outdoors for a long time. Too low a dosage will lead to a decrease in the adhesion and water resistance of the coating, while too high a dosage may affect the air permeability and hardness of the coating.
[0075] In the present invention, the mass ratio of the foaming agent to the thickener is preferably 0.1-0.3:0.07, more preferably 0.2:0.07; the mass ratio of the foaming agent to the foam stabilizer is preferably 0.1-0.3:0.5, more preferably 0.2:0.5; the mass ratio of the foaming agent to the acrylic emulsion is preferably 0.1-0.3:1, more preferably 0.2:1.
[0076] The raw material for preparing the non-expanding fire-retardant coating for fiber-reinforced composite materials provided by the present invention comprises water in a mass percentage of 12-15%, preferably 13-14%, and more preferably 13.4-13.5%.
[0077] The non-expandable fireproof coating for fiber-reinforced composite materials provided by the present invention is based on geopolymer gelling materials, various lightweight heat-insulating fillers and flame retardants are dispersed therein, and the bonding strength is improved by adding redispersible latex powder and polyethylene, and the strength at room temperature and high temperature is improved by hydrophobically modified expanded perlite. In addition, the working performance and durability are improved by adding various additives.
[0078] The present invention also provides a method for preparing the non-expanding fire retardant coating for fiber-reinforced composite materials described in the above technical solution, comprising the following steps:
[0079] A binder other than the activator, a heat-insulating filler other than the hollow glass microspheres, and a flame retardant are first mixed to obtain a base material;
[0080] The base material, foaming agent, thickener and foam stabilizer are mixed for the second time to obtain a dry material;
[0081] The dry material and hollow glass microspheres are mixed for a third time, and then an activator, acrylic emulsion and water are added for a fourth mixing to obtain a mixture;
[0082] The mixed material and the fibers are mixed and dispersed to obtain a non-expanding fire retardant coating for fiber-reinforced composite materials.
[0083] In the present invention, the first mixing is preferably performed under low-speed stirring; the rate of the low-speed stirring is preferably 130-150 rpm, more preferably 140 rpm; the time of the first mixing is preferably 3-5 min, more preferably 3 min.
[0084] In the present invention, the second mixing is preferably carried out under low-speed stirring; the low-speed stirring rate is preferably 130-150 rpm, more preferably 140 rpm; the second mixing time is preferably 1-3 min, more preferably 1 min; the equipment used for the second mixing is preferably a stirring pot. During the second mixing process, the present invention preferably uses a cover plate to cover the top of the stirring pot to prevent the added additive from splashing out.
[0085] In the present invention, the third mixing is preferably carried out by manual stirring first, and then by low-speed stirring; the rate of the low-speed stirring is preferably 130-150rpm, more preferably 140rpm; the time of the low-speed stirring is preferably 1min; the equipment used for the third mixing is preferably a stirring pot. During the third mixing process, the present invention preferably uses a cover plate to cover the top of the stirring pot. Since the density of the hollow glass microspheres is extremely low, they are first dispersed in the dry material by manual stirring, and then stirred at a low speed.
[0086] In the present invention, the acrylic emulsion and water are preferably used in the form of a mixture of acrylic emulsion and water; the preparation method of the mixture of acrylic emulsion and water is preferably to mix and stir the acrylic emulsion and water uniformly; the stirring rate is preferably 30 to 50 rpm, more preferably 30 rpm.
[0087] In the present invention, the fourth mixing is preferably firstly stirring at a low speed and then stirring at a high speed; the rate of the low-speed stirring is preferably 130-150rpm, more preferably 140rpm; the time of the low-speed stirring is preferably 1-2min, more preferably 1min; the rate of the high-speed stirring is preferably 270-300rpm, more preferably 290rpm; the time of the high-speed stirring is preferably 2-3min, more preferably 2min; the equipment used for the fourth mixing is preferably a stirring pot; after the high-speed stirring, the present invention preferably uses a spatula to scrape the unmixed materials on the pot wall and blades of the stirring pot into the stirred materials in the stirring pot. In the fourth mixing process, the low-speed stirring is first used to make the dry material fully contact with the liquid, and at the same time, it can also prevent the material from splashing out during high-speed stirring.
[0088] In the present invention, the mixing and dispersion of the mixture and the fibers are preferably performed as follows: under low-speed stirring, the fibers are gradually added to the mixture, and then high-speed stirring is performed for dispersion; the gradual addition is preferably performed in small amounts and multiple times; the low-speed stirring rate is preferably 130-150 rpm, more preferably 140 rpm; the high-speed stirring rate is preferably 270-300 rpm, more preferably 290 rpm; the high-speed stirring time is preferably 3-5 min, more preferably 5 min; the present invention preferably manually disperses the clumped fibers and then adds them to the mixture to prevent the fibers from clumping.
[0089] The present invention also provides the use of the non-expanding fire retardant coating for fiber-reinforced composite materials described in the above technical solution or the non-expanding fire retardant coating for fiber-reinforced composite materials prepared by the preparation method described in the above technical solution in fire prevention of fiber-reinforced composite materials.
[0090] The present invention also provides a non-expansive fireproof coating, comprising the following steps: applying the non-expansive fireproof coating for fiber-reinforced composite materials on the surface of a concrete structure reinforced with fiber-reinforced composite materials, and performing curing to obtain the non-expansive fireproof coating;
[0091] The non-expanding fire retardant coating for fiber-reinforced composite materials is the non-expanding fire retardant coating for fiber-reinforced composite materials described in the above technical solution or the non-expanding fire retardant coating for fiber-reinforced composite materials prepared by the preparation method described in the above technical solution.
[0092] In the present invention, the coating method is preferably manual application or spraying, more preferably manual application; the curing temperature is preferably 25-35°C, more preferably 25-30°C; the curing humidity is preferably 70-85%, more preferably 70-80%; the curing time is preferably 14-28d, more preferably 28d. The present invention does not specifically limit the thickness of the non-expanding fire retardant coating, which can be determined according to the requirements of the use scenario. In the application example of the present invention, the thickness of the non-expanding fire retardant coating is 30mm.
[0093] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0094] Example 1
[0095] The raw materials for preparing the non-expanding fire retardant coating for fiber-reinforced composite materials described in Example 1 are shown in Table 1:
[0096] Table 1 Preparation materials of non-expanding fire retardant coating for fiber-reinforced composite materials described in Example 1
[0097]
[0098] Among them, the D50 particle size of kaolin is 9.1μm; the D50 particle size of fly ash is 5.2μm; the particle size of CA80 high alumina cement is D50 particle size = 14.5μm; the alkali activator is a mixed solution of sodium silicate and sodium hydroxide, and the modulus of the alkali activator is 1.6M. The specific preparation process is as follows: taking the preparation of 1L alkali activator as an example, first, weigh 64g of sodium hydroxide and dissolve it in an appropriate amount of water, then add 128g of water glass with a mass ratio of 2:1, stir evenly, and finally, add water to adjust the total volume to 1L; the particle size of the redispersible latex powder is 5μm; the particle size of the polyvinyl alcohol powder is 120 mesh, and the number average molecular weight of the polyvinyl alcohol powder is 80000; the D50 particle size of the expanded vermiculite is 226.6μm; the hydrophobically modified expanded perlite The particle size is 1-2 mm, and the expanded perlite is hydrophobically modified by using 5wt% isobutyltriethoxysilane. The preparation process is as follows: taking the modification of 1000g expanded perlite as an example, first, 62.5g of 40wt% isobutyltriethoxysilane solution and 437.5g of water are mixed to obtain a 5wt% isobutyltriethoxysilane solution, and then the mixture is allowed to stand for 1 hour to allow the hydrophobic agent to be fully hydrolyzed. Then, 1000g of expanded perlite and 500g of 5wt% isobutyltriethoxysilane solution are fully mixed in a disc-shaped container, and soaked at room temperature for 24 hours to allow the hydrophobic agent to fully react with the hydroxyl group on the surface of the expanded perlite. Finally, the liquid is filtered out, and the modified perlite is placed in a 100°C blast drying oven and dried to constant weight to obtain hydrophobically modified expanded perlite.
[0099] The particle size of sepiolite is 350-400 μm; the hollow glass microspheres are composed of two types of hollow glass microspheres with a particle size of D50 = 65 μm and a particle size of D50 = 40 μm, the volume ratio of the two types of hollow glass microspheres with a particle size of D50 = 65 μm and a particle size of D50 = 40 μm is 7:3, the wall thickness of the hollow glass microspheres is 2 μm, and the true density of the hollow glass microspheres with a particle size of D50 = 40 μm is 0.6 g / cm 3 , bulk density is 0.35g / cm 3 The true density of hollow glass microspheres with a particle size of D50 = 65 μm is 0.2 g / cm 3 , bulk density is 0.1g / cm 3 , the length of the glass fiber is 6mm and the diameter is 15μm; the foaming agent is sodium a-olefin sulfonate; the foam stabilizer is calcium stearate and a lightweight partition board foam stabilizer (Luoyang Tongrun Nano Technology Co., Ltd.) in a mass ratio of 1:1; the thickener is cellulose ether; the solid content of the acrylic emulsion is 50%;
[0100] The preparation method of the non-expanding fire retardant coating for fiber-reinforced composite materials is as follows:
[0101] Step 1: First, add the binder except the water glass activator, the heat insulation filler except the hollow glass microspheres, and the flame retardant into a stirring pot for dry mixing, and stir at a low speed of 140 rpm for 3 minutes to obtain a base material;
[0102] Step 2: Add a foaming agent, a thickener and a foam stabilizer to the base material, continue stirring at a low speed of 140 rpm for 1 minute, and use a cover plate to cover the top of the stirring pot to prevent the added additives from splashing out to obtain a dry material;
[0103] Step 3: Add hollow glass microspheres to the dry material. Due to its extremely low density, first use manual stirring to disperse it in the dry material, and then stir it at a low speed of 140 rpm for 1 minute. It also needs to be covered with a cover plate to obtain a hollow glass microsphere mixture;
[0104] Step 4: Mix the acrylic emulsion and water and stir evenly at 30 rpm to obtain a mixed solution of acrylic emulsion and water;
[0105] Step 5: Add the water glass activator and the mixture of acrylic emulsion and water into the hollow glass microbead mixture in the stirring pot, first stir at a low speed of 140rpm for 1min to allow the dry material to fully contact the liquid and prevent the material from splashing out during high-speed stirring, then stir at a high speed of 290rpm for 2min, and use a spatula to scrape the unmixed materials on the wall and blades of the stirring pot into the mixed materials in the stirring pot to obtain a mixture;
[0106] Step 6: Add glass fiber to the mixture at a low speed of 140 rpm. When adding glass fiber, add it gradually in small amounts and multiple times, and manually disperse the clumped fibers before adding them, and stir again at a high speed of 290 rpm for 5 minutes to fully disperse the fibers in the slurry to obtain a non-expanding fire retardant coating for fiber-reinforced composite materials.
[0107] Example 2
[0108] The difference from Example 1 is that 5 wt % of flame retardant is used.
[0109] Example 3
[0110] The difference from Example 1 is that 2.5 parts by mass of CA80 high alumina cement in Example 1 is replaced by 5 parts by mass.
[0111] Comparative Example 1
[0112] The difference from Example 1 is that no hollow glass microspheres are added.
[0113] Comparative Example 2
[0114] The difference from Example 1 is that no hydrophobically modified expanded perlite is added.
[0115] Comparative Example 3
[0116] The difference from Example 1 is that no hydrophobically modified expanded perlite and hollow glass microspheres are added.
[0117] Comparative Example 4
[0118] The difference from Example 1 is that the hydrophobically modified expanded perlite is replaced by expanded perlite.
[0119] Comparative Example 5
[0120] The difference from Example 1 is that half of the hydrophobically modified expanded perlite in Example 1 is replaced by expanded perlite that is not hydrophobically modified.
[0121] Application Example 1
[0122] The non-expanding fire retardant coating for fiber reinforced composite materials prepared in Example 1 was applied to the surface of a concrete structure reinforced with fiber reinforced composite materials by manual coating, and cured at 25° C. and 70% humidity for 28 days to obtain a non-expanding fire retardant coating with a thickness of 30 mm.
[0123] Application Example 2
[0124] The difference from Application Example 1 is that the non-expanding fire retardant coating for fiber reinforced composite materials prepared in Example 1 is replaced by the non-expanding fire retardant coating for fiber reinforced composite materials prepared in Example 2, and the rest of the content is consistent with Application Example 1.
[0125] Application Example 3
[0126] The difference from Application Example 1 is that the non-expanding fire retardant coating for fiber reinforced composite materials prepared in Example 1 is replaced by the non-expanding fire retardant coating for fiber reinforced composite materials prepared in Example 3, and the rest of the content is consistent with Application Example 1.
[0127] Comparative application example 1
[0128] The difference from Application Example 1 is that the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 is replaced by the non-expanding fire retardant coating prepared in Comparative Example 1, and the rest of the contents are consistent with Application Example 1.
[0129] Comparative Application Example 2
[0130] The difference from Application Example 1 is that the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 is replaced by the non-expanding fire retardant coating prepared in Comparative Example 2, and the rest of the contents are consistent with Application Example 1.
[0131] Comparative Application Example 3
[0132] The difference from Application Example 1 is that the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 is replaced by the non-expanding fire retardant coating prepared in Comparative Example 3, and the rest of the contents are consistent with Application Example 1.
[0133] Performance Testing
[0134] (1) The density of the coating formed by the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 was tested. The specific test method was as follows: a 50 mm × 50 mm × 50 mm cube was used to measure the dry density. After curing for 28 days, the specimen was placed in a drying oven at 105° C. and dried to constant weight. The side length b was then measured with a vernier caliper. The mass m was then weighed. The density was calculated using the following formula:
[0135]
[0136] The density of the coating formed by the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 of the present invention is 686.8 kg / m 3 .
[0137] (2) The compressive strength of the coating formed by the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 was tested. Specifically, the compressive strength test was also carried out using a 50 mm × 50 mm × 50 mm cube. After curing for 28 days, it was placed in a drying oven at 60°C for 12 hours and calcined at 800°C for 1 hour. Then, a 5 t MTS testing machine was used for the compressive test. The loading rate was 200 N / min. The compressive test was as follows: Figure 1 shown.
[0138] The non-expanding fire-retardant coating for fiber-reinforced composite materials prepared by the present invention has a compressive strength of 1.31 MPa at room temperature, and a compressive strength of 3.81 MPa after calcination at 800° C. for one hour.
[0139] (3) The flexural strength of the coating formed by the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 was tested. Specifically, the flexural strength test was performed using a 160 mm × 40 mm × 40 mm test piece, which was placed in a drying oven at 60° C. for 12 h after curing for 28 days, and then subjected to a flexural test using a standard compression flexural test machine at a loading rate of 10 mm / min. The flexural test was performed as follows: Figure 2 shown.
[0140] The flexural strength of the coating formed by the non-expansion fire retardant coating for fiber-reinforced composite materials prepared by the present invention is 1.05 MPa.
[0141] (4) Bond strength: The bond strength in the present invention refers to the bond strength between the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 and the cement mortar substrate. A 70 mm × 70 mm × 20 mm cement mortar test block was used and a 5 mm thick coating was applied on the surface of the test block. After curing for 28 days, the bond strength was tested by a direct pull test. The bond strength direct pull test is as follows: Figure 3 shown.
[0142] The non-expansion fire retardant coating for fiber-reinforced composite materials prepared by the present invention forms a coating with a bonding strength of 0.39 MPa.
[0143] (5) Water resistance: A fiber-reinforced low-alkalinity cement building slab was used as the base plate, with a size of 150 mm × 70 mm × 6 mm. A 5 mm thick non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Example 1 was applied to the base plate surface to form a coating. After curing for 28 days, the edges and back of the specimen were sealed with a mixed solution of paraffin and rosin (mass ratio of 1:1). Then 2 / 3 of the specimen was immersed in water. After immersion in water for 28 days, no cracks appeared on the surface. The water resistance test was as follows: Figure 4 shown.
[0144] (6) High and low temperature cycle: The specimens used in the high and low temperature resistance test are the same as those used in the water resistance test. The cycle process is as follows: store them in an environment of -20℃±2℃ for 3 hours, then store them in an environment of 50℃±2℃ for 3 hours, and repeat the above process 20 times.
[0145] The non-expanding fire-retardant coating prepared by the present invention has no surface cracks after 20 cycles.
[0146] (7) Fire resistance: A simplified version of the fire resistance limit test was adopted, and the test substrate was a 150mm×150mm×25mm concrete block. Then, a 30mm thick layer of the non-expanding fire retardant coating for fiber-reinforced composite materials prepared in Examples 1 to 3 and the fire retardant coating of Comparative Example 4 was applied on the surface, respectively. The surface was smoothed and then cured for 28 days. The test equipment used was a multifunctional box furnace purchased by the laboratory. The equipment can achieve a heating process close to that described by the ISO standard heating curve. During the test, the coating surface was facing the inside of the furnace and directly exposed to the high temperature environment. Then, the temperature change at the interface between the coating and the concrete substrate was recorded by a thermocouple pre-buried in the specimen. The test schematic is shown in the figure. Figure 5 As shown, the results are Figure 6 The temperature in the furnace refers to the temperature of the heated surface. The concrete slab simulates the thickness of the concrete cover, so the temperature on the back of the concrete block is the temperature of the reinforcement under fire conditions.
[0147] In the fire resistance test, the temperature change of the back side of the coating under fire was recorded. Figure 6It can be seen that the temperature curves of Examples 1 to 3 in the early stage of fire all have a low temperature section with a temperature less than 100°C for up to 60 minutes, and there is an obvious platform section with a temperature of about 100°C for up to 20 minutes, which is very beneficial for the FRP reinforced concrete system to continue to play a mechanical role under fire and not to be destroyed in a short time after the fire. This provides more sufficient time for people to escape and rescue under fire, and can effectively reduce the hazards and losses caused by fire. The temperature of the fire retardant coating of Comparative Example 4 is less than 100°C for only 46 minutes, and there is no significant platform section, which shows that the non-expansive fire retardant coating for fiber reinforced composite materials prepared by the present invention has better thermal insulation performance.
[0148] (8) The mechanical properties of the coatings formed by the non-expanding fire retardant coatings for fiber-reinforced composite materials prepared in Examples 1 to 3 and the fire retardant coating of Comparative Example 4 were tested. The results are shown in Table 2.
[0149] Table 2 Mechanical properties
[0150]
[0151] As shown in Table 2, compared with the fire retardant coating of Comparative Example 4, the coating formed by the non-expanding fire retardant coating for fiber reinforced composite materials prepared by the present invention has higher compressive strength, bonding strength and flexural strength. In addition, the strength test shows that the strength of Example 1 is nearly doubled after being subjected to a high temperature of 800°C for one hour, indicating that in a fire environment, the coating can maintain mechanical properties and greatly reduce the problem of decreased fire retardant performance caused by coating shedding.
[0152] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A non-intumescent fire retardant coating for fiber-reinforced composite materials, characterized in that: In terms of mass percentage, the raw materials include 50-58% of binder, 20-24% of thermal insulation filler, 5-10% of flame retardant, 0.3-0.5% of fiber, 0.3-0.6% of auxiliary agent and 12-15% of water; The binder includes metakaolin, fly ash, CA80 high-alumina cement and an activator, or includes metakaolin, fly ash, CA80 high-alumina cement, an activator and an organic binder; The organic binder includes redispersible latex powder and / or polyvinyl alcohol powder; The heat-insulating filler includes expanded vermiculite, hydrophobically modified expanded perlite, sepiolite and hollow glass microspheres; The flame retardant includes aluminum hydroxide and magnesium hydroxide; The fibers include glass fibers; The auxiliary agents include a foaming agent, a thickener, a foam stabilizer and acrylic emulsion.
2. The non-intumescent fire retardant coating for fiber-reinforced composite materials according to claim 1, characterized in that: The particle size of the hydrophobically modified expanded perlite is 1-2 mm; the hydrophobically modified expanded perlite is isobutyltriethoxysilane modified expanded perlite.
3. The non-intumescent fire retardant coating for fiber-reinforced composite materials according to claim 1, characterized in that: The hollow glass microspheres include two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm; the volume ratio of the two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm is 5-7:3-5.
4. The non-intumescent fire retardant coating for fiber-reinforced composite materials according to claim 1, characterized in that: The foaming agent includes sodium α-olefin sulfonate; the foam stabilizer includes calcium stearate and / or a lightweight partition board foam stabilizer; and the thickener includes cellulose ether.
5. The non-intumescent fire retardant coating for fiber-reinforced composite materials according to claim 1 or 4, characterized in that: The mass ratio of the foaming agent to the thickener is 0.1-0.3:0.07; the mass ratio of the foaming agent to the foam stabilizer is 0.1-0.3:0.5; the mass ratio of the foaming agent to the acrylic emulsion is 0.1-0.3:1, and the solid content of the acrylic emulsion is 40-60%.
6. The non-intumescent fire retardant coating for fiber-reinforced composite materials according to claim 1, characterized in that: The mass ratio of the metakaolin to the redispersible latex powder is 70:0-5; the mass ratio of the metakaolin to the polyvinyl alcohol powder is 70:0-1.
5.
7. The non-intumescent fire retardant coating for fiber-reinforced composite materials according to claim 1, characterized in that: The mass ratio of the metakaolin, fly ash and CA80 cement is 50-70:20-48:2-3; the mass ratio of the metakaolin and the activator is 70:123-135.
8. The method for preparing a non-expanding fire retardant coating for fiber-reinforced composite materials according to any one of claims 1 to 7, characterized in that: The following steps are involved: A binder other than the activator, a heat-insulating filler other than the hollow glass microspheres, and a flame retardant are first mixed to obtain a base material; The base material, foaming agent, thickener and foam stabilizer are mixed for the second time to obtain a dry material; The dry material and hollow glass microspheres are mixed for a third time, and then an activator, acrylic emulsion and water are added for a fourth mixing to obtain a mixture; The mixed material and the fibers are mixed and dispersed to obtain a non-expanding fire retardant coating for fiber-reinforced composite materials.
9. Use of the non-expanding fire retardant coating for fiber-reinforced composite materials according to any one of claims 1 to 7 or the non-expanding fire retardant coating for fiber-reinforced composite materials prepared by the preparation method according to claim 8 in fire prevention of fiber-reinforced composite materials.
10. A method for preparing a non-intumescent fire retardant coating, characterized in that: The method comprises the following steps: coating a non-expanding fire-retardant coating for fiber-reinforced composite materials on the surface of a concrete structure reinforced with fiber-reinforced composite materials, and performing curing to obtain a non-expanding fire-retardant coating; The non-expanding fire retardant coating for fiber-reinforced composite materials is the non-expanding fire retardant coating for fiber-reinforced composite materials described in any one of claims 1 to 7 or the non-expanding fire retardant coating for fiber-reinforced composite materials prepared by the preparation method described in claim 8.
Citation Information
Patent Citations
Alkali slag tunnel fireproof coating and use method thereof
CN104194426A
Thick coating type potassium-based geopolymer fireproof coating for steel structure and preparation method of thick coating type potassium-based geopolymer fireproof coating
CN114479524A
Fireproof coating for steel structure as well as preparation method and use method of fireproof coating
CN115044232A
Cited By
Fabricated wall cementing material prepared from multi-element solid waste and preparation method of fabricated wall cementing material
CN120794463A
A cementing material for preparing a multi-element solid waste assembled wall and a preparation method thereof
CN120794463B
Geopolymer-based aerogel fireproof coating as well as preparation method and application thereof
CN121064661A